Diversion of Nazhir Waqf; Analysis of BWI Regulation No. 1 of 2020 - Amin, Ibnu; Firdaus, Firdaus; Elfia, Elfia; Lendrawati, Lendrawati (Institut Agama Islam Negeri (IAIN) Curup, 2024)
Diversion of Waqf Nazhir Analysis of the BWI No. 1 of 2020 concerning Guidelines for Waqf Property Management, this study aims to elaborate on waqf, dismissal and replacement of waqf nazhirs. This research uses library research presented descriptively with a normative legal approach. Data collected using literature on waqf fiqh and waqf legislation in Indonesia. This study shows that referring to the history of waqf which is used as the basis of waqf, namely the act of Umar bin Khattab endowment of land in Khaibar that Umar was ordered by the Messenger of Allah to withhold the principal and alms the proceeds. So the definition of waqf is the legal act of a person or group of people or legal entity (wakif) that separates part of his property and institutionalizes it forever for the benefit of worship or other public affairs in accordance with Islamic teachings. Nazhir plays a role in managing and utilizing waqf assets to be productive, nazhir is required to have scientific competence of amaliah, scientific shari'iyah and da'wiyah. Nazhir was given guidance and can also be dismissed by BWI if he does not carry out his duties and/or violates the prohibitions stipulated by laws and regulations